Item Analysis of Reading Comprehension Test: A Study of Test Scores Interpretation - Risna Saswati (Scope : Journal of English Language Teaching, 2021)
This study sheds lights on the effectiveness of multiple choice of reading comprehension test items in measuring learners’ reading comprehension competence. This study applies descriptive quantitative method of research that uses statistical analysis to measure the effectiveness of the individual test item. The study uses the theories of multiple-choice test type and Item Analysis (IA). The data were taken from multiple choice test type of reading comprehension test given to 51 freshman students attending Literal Reading class. The test had 31 numbers comprising the questions of Text A, B and C. The reading comprehension test items were measured by the procedure of Item Analysis using the Item Facility, Item Discrimination and Distractor Efficiency. The result of this study is there are 13 items in reading comprehension test which are in need to be reviewed by the teachers. It is needed to be revised since the test is intended to be put in the question bank and be used repeatedly for the future use.